The Qu'ran Manuscripts in the al-Haram al-Sharif Islamic Museum, Jerusalem: By Khader Salameh (Reading, UK: Garnet Publishing, 2001. 190 pages.) (American Journal of Islam and Society, 2003)
Founded in 1922 and moved to al-Haram al-Sharif in 1929, the IslamicMuseum in Jerusalem houses artifacts covering nearly all oflslamic historyand originating in North Africa, Turkey, Iran, Central Asia, and theMiddle East.This beautifully illustrated volume, published with the support ofUNESCO in both English and Arabic, treats a small part of the Museum'scollection: a selection of its Qur'an manuscripts. The work, divided intothree parts, first introduces the Islamic Museum and its collection, thenprovides background information concerning relevant textual and art history,and finally presents 3 I Qur'an manuscripts in detail.Part One, "The Islamic Museum," gives an overview of theMuseum's holdings, including wood, metalwork, ceramics, glass, tex tiles,coins, stone inscriptions and architectural elements, and documents.Most of the artifacts are material salvaged from repairs to the haram areaor objects from the endowments of the Aqsa mosque and madrasahs inJerusalem, Nablus, and Hebron. The collection includes many exquisitepieces: Umayyad floral woodwork panels from the al-Aqsa Mosque, astriking glass mosque lamp of the Mamluk amir Tankiz from Hebron, andthe salvaged remains of Nur al-Din's pulpit, built in Aleppo in 564/1168and brought to the Aqsa Mosque in 583/1187 by Salah al-Din after hisconquest of Jerusalem. (Unfortunately, the ornate wooden pulpit wasnearly destroyed by arson in I 969.)Part Two, "Background," treats Arabic calligraphy, illumination,bindings, and the textual history of the Qur'an. Kufic, an old, squarescript said to derive from stone inscriptions, is used for the text of the old estQur'an manuscript in the collection and for headings and panels inlater manuscripts.The bulk of the manuscripts are written in the more cursive Naskhiscript, which became popular by the tenth century, and the similar buttaller Thuluth and Muhaqqaq. A number of the collections manscriptsfrom North Africa are written in Maghribi script, which derives fromKufic and differs significantly from the common eastern scripts. This volumeallows the reader to view some stunning examples of illumination ...